EMPIRICAL STUDY OF THE APPLICATION OF CAN- ING AS A PUNISHMENT FOR VIOLATORS OF IS- LAMIC LAW IN ACEH PROVINCE (Case Study at the Satpol PP Office and Wilayatul Hisbah of Simeulue District) - Mus Mulyadi; Rahmayanti; Muhammad Arif Sahlepi (International Journal of Society and Law, 2025)
Aceh is a province with special status in Indonesia that has special authority in the imple- mentation of Islamic law, as stipulated in Law No. 11 of 2006 concerning the Government of Aceh. One form of its implementation is Qanun Aceh No. 6 of 2014 on Jinayat Law, which regulates a number of offences, including maisir (gambling), with penalties in the form of flogging, fines, or im- prisonment. This study aims to examine the application of flogging for maisir offenders in Simeulue Regency, covering the legal basis, implementation procedures, and level of effectiveness. The research questions include: (1) how flogging is applied to maisir offenders; (2) what are the stages of implemen- tation; and (3) to what extent is it effective in reducing violations. The research uses a qualitative de- scriptive method with a socio-legal approach. Data was obtained through literature review, field obser- vation, and interviews with Satpol PP and Wilayatul Hisbah officials, the Sharia Court, the prosecutor's office, and community leaders. The findings show that the application of flogging has a strong consti- tutional basis and is in accordance with the principles of Sharia law. The punishment is carried out openly in accordance with criminal procedure law and under the supervision of medical personnel. Statistics from the last five years show a decline in gambling cases from 11 cases in 2020 to 3 cases in mid-2024, reflecting a deterrent effect and increased public awareness of the law. However, obstacles such as limited human resources, supporting facilities, and cultural factors remain challenges. Overall, flogging is considered effective in reducing gambling offences, but institutional strengthening, inter- agency coordination, and continuous legal socialisation are still needed.